Educators' narratives about belonging and diversity in northern Finland early childhood education - Janna Juutinen; Riikka Kess (University of Aberdeen, School of Education, 2019)
This study focuses on belonging and diversity in early childhood education (ECE) in northern Finland. The concept of belonging is understood as involving dynamic processes that are constructed in the multiple relations of everyday life (Juutinen, 2018; Yuval-Davis, 2011). The concept of cultural diversity can be seen through various factors, such as language, ethnicity, nationality, but also socioeconomic background, religion, gender, sexual orientation, age and ability. The study aims to deepen the understanding about belonging and diversity by asking this question: How do educators co-create the understanding about belonging and diversity in the northern ECE settings? The research material consists of peer interviews between 24 educators (Devotta et al., 2016). Each peer interview was recorded, where a pair of educators shared their experiences about belonging and diversity in ECE. The peer interviews were analysed using the three-sphere context model (Zilber, Tuval-Mashiach, and Lieblich, 2008). The findings indicated that educators approached their conceptual understanding by encountering others, intertwining various perspectives and mapping belonging and diversity. The study contributes to the scientific discussion on the conceptualisation of belonging and diversity in ECE. The ethical issues and researchers' roles are discussed.